PENERAPAN QR CODE PADA PEMBELAJARAN KONSENTRASI KEAHLIAN DPIB UNTUK MENINGKATKAN HASIL BELAJAR PRODUK KREATIF DAN KEWIRAUSAHAAN SISWA KELAS XI DPIB 1 SMKN 5 MEDAN - Mia Sara; Kinanti Wijaya (STKIP Subang, 2026)
Vocational education plays an important role in preparing competent, independent,and competitive human resources in the workplace and business world. However,the effectiveness of learning in Vocational High Schools (SMK) still faces variouschallenges, one of which is the limited use of innovative and interactive learningmedia. This has an impact on low student learning outcomes. Teachers do not usemedia that attract students' attention to learn. This study aims to apply QR learningmedia to improve student learning outcomes. The study is a CAR consisting of 2cycles where each cycle has 2 meetings. Each cycle consists of 4 stages, namelyplanning, implementation, observation, and reflection. The data for this study wereobtained from the learning outcome test of 32 students of class XI SPIB. The testinstrument used was the test validity test, test difficulty index, item discriminationpower, and test reliability. The results of this study showed an increase in studentlearning outcomes with an average in cycle I of 78.26 and cycle II of 86.69 with anincrease in learning outcomes of 8.43% and classical completeness of studentlearning outcomes of 87.5%. This shows that QR learning media can improve thelearning outcomes of class XI students at SMK Negeri 5 Medan.